Political Networks across the Globe - Simon Commander; Stavros Poupakis (Institute of Labor Economics (IZA), 2020)
Political networks are an important feature of the political and economic landscape of countries. Despite their ubiquity and significance, information on such networks has proven hard to collect due to a pervasive lack of transparency. However, with the advent of big data and artificial intelligence, major financial services institutions are now actively collating publicly available information on politically exposed persons and their networks. In this study, we use one such data set to show how network characteristics vary across political systems. We provide results from more than 150 countries and show how the format of the network tends to reflect the extent of democratisation of each country. We also outline further avenues for research using such data.
Keywords: D72; H11; P26; P36; N44; 330; political networks; rent-seeking; democratic consolidation